The West at War - Watson, Bradley C. S. (Lexington Books, 2006)
In The West at War, Bradley C. S. Watson brings together renowned scholars and public policy experts to reflect on perhaps the most pressing problem of our time—the West's increasingly bloody conflict with forces that seek nothing less than its destruction. In eleven provocative chapters, contributors deal with the internal challenges and external conflicts facing Western civilization in the context of the 'war on terror.' Ranging from the nature of Islam and the West, to ethics and terror, to the western way of warfare, the volume deals thematically with major issues raised by this conflict in a way that no other single-volume does. Contributors bring to bear arguments on the philosophic, political, religious, ethical, and policy dimensions of the war. As the title of the book suggests, this conflict implicates all of Western civilization, demonstrating that this not merely an 'American' concern.